THE NECESSITY OF USING DIGITAL TECHNOLOGIES IN TEACHING ENGLISH (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
Without doubt that technology has a role in children, teens, and adults' everyday lives. This has an immediate effect on how students and teachers interact. According to the statement above this article provides some arguments of beneficial features of utilizing digital tools at English lesson.